Subacute Paget–Schroetter with rapid recurrence and concurrent pulmonary emboli: a case report - O’Toole, Francis; Kemp Van Ee, Shantele; Madison, Danielle; DiVincenzo, Kathryn; Tran, Khoa; Mohamed, Alaa (Frontiers in Surgery, 2025)
Effort thrombosis, also known as Paget–Schroetter syndrome, is a rare venous manifestation of Thoracic Outlet Syndrome, primarily affecting young adults who perform repetitive overhead motions, such as athletes and trades workers. Stasis occurs when surrounding tissues encroach upon venous flow through the subclavian and/or axillary veins, manifesting as pain, swelling, and discoloration, with a potential for pulmonary embolism and other sequelae if left untreated. We present a 22-year-old male, avid weightlifter, with initial and recurrent left subclavian thrombosis and right pulmonary emboli, who did not respond to mechanical thrombectomy and anticoagulation, requiring surgical reconstruction at the thoracic outlet only two weeks after initial presentation. While there are no consensus guidelines for the management of Paget–Schroetter syndrome, aggressive management of acute thrombi demonstrates low rates of recurrence. There is less guidance regarding subacute thrombi. We advocate for a similarly aggressive approach to management of subacute thrombi to prevent recurrence and complications such as pulmonary embolism, post-thrombotic syndrome, and vessel fibrosis.